A mouse model of rapidly progressive fatal haemorrhagic pneumonia caused by Stenotrophomonas maltophilia. (December 2020) - Imoto, Waki; Kaneko, Yukihiro; Yamada, Koichi; Kuwabara, Gaku; Yamairi, Kazushi; Shibata, Wataru; Oshima, Kazuhiro; Niki, Makoto; Nakaie, Kiyotaka; Watanabe, Tetsuya; Asai, Kazuhisa; Kawaguchi, Tomoya; et al.
Highlights: Mouse model of haemorrhagic pneumonia caused by Stenotrophomonas maltophilia . Haemorrhagic pneumonia progressed rapidly after a certain time point in infection. Early levofloxacin and moxifloxacin treatment improved the survival rate. Quinolone antibacterials decreased the bacterial load in the lungs and cardiac blood. Moxifloxacin was not inferior to levofloxacin in vivo. Abstract: Objectives: Stenotrophomonas maltophilia causes severe haemorrhagic pneumonia with a reported mortality rate of 100%. However, currently there are no available mouse models of haemorrhagic pneumonia. In the present study, we generated a mouse model of haemorrhagic pneumonia and subjected the animals to treatment with levofloxacin and moxifloxacin to determine whether this model can be used to determine therapeutic effects. Methods: Stenotrophomonas maltophilia was transtracheally administered to mice immunosuppressed with cyclophosphamide. We confirmed the pathological status of the S. maltophilia isolate and assessed whether the therapeutic effects of quinolone antibiotics could be studied using the model. Levofloxacin and moxifloxacin were administered to evaluate survival rate, bacterial load in the lungs and cardiac blood, as well as pathological changes in diseased lungs compared with those of the control group. Results: Haemorrhagic pneumonia developed within 16–24 h after bacterial infection and was confirmed pathologically. Levofloxacin and moxifloxacin significantly improved survival rates, decreased the bacterial load in lungs and cardiac blood, and improved haemorrhagic pneumonia as indicated by pathological examination. Conclusions: We established a mouse model of rapidly progressive fatal haemorrhagic pneumonia caused by S. maltophilia that is useful for determining the therapeutic effect of various agents. We believe that this model will prove useful to further elucidate the mechanisms underlying haemorrhagic pneumonia as well as in the design and development of novel therapeutic modalities and targets.